Investigation of physical-mechanical properties and impact on soil of granulated manure compost fertilizers - Mieldažys, Ramūnas; Jotautienė, Eglė; Jasinskas, Algirdas; Pekarskas, Juozas; Zinkevičienė, Raimonda (Journal of Environmental Engineering and Landscape Management, 2019)
In recent years, the European countries recycle only 5−7% of bio-waste. One activity of the biological waste disposal is granulation. The production of fertilizer from animal manure with supplement represents an important area of environmentally friendly bio-fertilizer production. This paper presents an investigation of estimation manure compost physical-mechanical properties for reuse of organic waste − cattle and cow manure, sugar production waste − molasses through new technology pellets production and of granulated fertilizer impact on soil. The experimental manure samples produced by industrial methods and samples produced in the laboratory from the time period of 2014 to 2017 were investigated. The following physical – mechanical characteristics were estimated: biometric indicators (dimensions, mass), volume and density of raw material and pellets, material and pellet’s humidity and pellets strength. Experiments results have shown that the difference in limit strength between experimental and industrial organic compost pellets was about 5%. Experiments of fertilizers on the impact on soil shown that the amount of nutrients added to the soil depends on the rate of the granulated compost fertilizer. As the norm increases, organic carbon, humus, mobile phosphorus and potassium increase in soil. Increases in soil fertility, improved agrochemical properties, soil organic matter accumulation and humus increase. Granulated compost fertilizers have no effect on soil acidity. The presented results could be helpful to the development of the fertilizing process by the granulated compost fertilizer for improvement of soil quality in small farms.